Impact of ethanol content on the scavenging activities of oak wood C‐glycosidic ellagitannins. Application to the evaluation of the nutritional status of spirits. Issue 3 (7th August 2013) - Vivas, Nicolas; Vivas de Gaulejac, Nathalie; Vitry, Christiane; Mouche, Claire; Kahn, Nadège; Nonier‐Bourden, Marie Françoise; Absalon, Christelle
<x xml:space="preserve">Abstract</x> As a consequence of their structure, ellagitannins have a high level of activity in terms of their oxidative properties. In particular, their scavenging activity is often presented as a noteworthy parameter, since polyphenols have a beneficial impact on human health. A large variety of spirits, brandies and whiskeys are aged in barrels or receive a wood extract rich in polyphenols. Although spirits (alcoholic beverages) represent a very dynamic market with significant growth, very few scientific papers have been published on this topic, or have justified specific research in this field. Firstly, the scavenging properties of ellagitannins when measured in a solution are presented. An oak wood extract was fractionated by gel chromatography to obtain different fractions with different polymeric levels. It is particularly clear that the oligomer forms are the most efficient by comparison with low‐weight and high‐weight fractions. A mixture of ellagitannins has a higher scavenging intensity than the pure molecule; this illustrates the synergic effect of polyphenols. The scavenging activity of different commercial spirits depends on the presence and quantities of ellagitannins. As an example, the percentage of scavenged superoxide anion radicals represents 70 and 18%, respectively, for spirits aged in a barrel (12 years) and white spirits. In a second step, details of the influence of ethanol on the antioxidant properties of ellagitannins are provided. In particular, alcohol increases the scavenging activity of ellagitannins from 0 to 25% vol., and higher concentrations present a certain degree of pro‐oxidant activity. The chemical study of ellagitannin scavenging properties in solution is confirmed by means of a specific in vitro investigation on the DNA extracted from cells, and directly on the cells. Copyright © 2013 The Institute of Brewing & Distilling